2016
DOI: 10.29101/crcs.v0i71.3990
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la formación inicial docente intercultural. Una revisión de la investigación

Abstract: El avance teórico y normativo de la educación en y para la diversidad cultural ha subrayado la necesidad de adecuar la formación inicial del profesorado al carácter plural de la realidad social y educativa. Este artículo centra su atención en las investigaciones empíricas desarrolladas entre 2005 y 2012 y destinadas a analizar el impacto que tienen los programas de formación inicial docente comprometidos con la diversidad cultural en los futuros profesores. Los resultados proporcionan información sobre los fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In their early research. Hinojosa and López (2016), analysed the impact of different training initiatives aimed at qualifying teachers in the management of cultural diversity. Following this, they concluded that, although the results of the reviewed investigations are inconclusive:…”
Section: Discussionmentioning
confidence: 99%
“…In their early research. Hinojosa and López (2016), analysed the impact of different training initiatives aimed at qualifying teachers in the management of cultural diversity. Following this, they concluded that, although the results of the reviewed investigations are inconclusive:…”
Section: Discussionmentioning
confidence: 99%